COMPARISON OF TWO INTRA-CANAL MEDICAMENTS ON THE INCIDENCE OF POST-OPERATIVE ENDODONTIC PAIN - Ali, Fatima; Yousaf, Ajmal; Daud, Zoobia; Hussain, Syed Muzammil; Ullah, Mohib; Rana, Muzammil Jamil Ahmed (Journal of Ayub Medical College Abbottabad, 2020)
Background: Post-operative pain is the most annoying factor for the patients for which different intra-canal medicaments are used. The aim of this study was to compare calcium hydroxide mixed with dexamethasone and triple antibiotic paste as intra-canal medicaments on the incidence of post-operative endodontic pain. Methods: This was a randomized controlled trail in which a total of 120 patients presenting to the department of Operative Dentistry AFID, Rawalpindi from 20-50 years of age from both gender presenting with acute apical periodontitis in their maxillary and mandibular central incisors were selected and randomly divided into three equal groups of 40 patients with the help of scientific random number table. Group A patients were given calcium hydroxide mixed with dexamethasone, group B patients were given triple antibiotic paste and in group C patients only cotton pellet was placed in the pulp chamber as a placebo. Endodontic therapy was initiated, following pulpectomy and disinfection, canals were prepared and intra-canal dressings were placed according to the allotted group and restored with cavit. Pain was recorded at 24, 48 and 72 hours using the visual analogue scale. Data was analysed using SPSS 21. Results: After 72 hours, 55% of group A patients had no pain, 47.5% patients in group B while in group C 17.5% of the patients reported no pain. Conclusion: Both calcium hydroxide combined with dexamethasone and triple antibiotic paste are effective in reducing post-operative pain in teeth with symptomatic irreversible pulpitis while placebo showed little reduction in pain. Keywords: Acute peri-apical periodontitis; Triple antibiotic paste; Post-operative pain